2014
DOI: 10.12693/aphyspola.125.93
|View full text |Cite
|
Sign up to set email alerts
|

Oscillator Strengths of Quantum Transitions in Spherical Quantum Dot GaAs/AlxGa1-xAs/GaAs/AlxGa1-xAs with On-Center Donor Impurity

Abstract: The investigation of the electron and hole energies and probability densities is performed for the cases with and without the donor hydrogenic impurity placed into the centre of quantum dot quantum well structures with dierent thicknesses of layers. The oscillator strengths of intra-and interband quantum transitions in GaAs/AlxGa1−xAs core/shell/well/shell spherical quantum dot with ionized on-center donor impurity are estimated. The oscillator strengths of quantum transitions non-monotonously depend on the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…During last few decades many theoretical and experimental studies on QDs have been performed within parabolic confinement models as well as beyond this approximation. Both the 2D and 3D QD's have been investigated in a framework of strict quantum-mechanical and semiclassical approaches, including also effects of an external magnetic field [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Semiclassical solutions for a two-electron QD in a magnetic field have been investigated in terms of action-angle variables using the classical adiabatic approximation [19].…”
Section: Introductionmentioning
confidence: 99%
“…During last few decades many theoretical and experimental studies on QDs have been performed within parabolic confinement models as well as beyond this approximation. Both the 2D and 3D QD's have been investigated in a framework of strict quantum-mechanical and semiclassical approaches, including also effects of an external magnetic field [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Semiclassical solutions for a two-electron QD in a magnetic field have been investigated in terms of action-angle variables using the classical adiabatic approximation [19].…”
Section: Introductionmentioning
confidence: 99%
“…The solutions of Eq. (6) are expressed as the products of spherical functions and Coulomb or Whittaker functions [2][3][4]7], and the solutions of Eq. 7are the products of spherical functions and Bessel functions.…”
Section: Formulation Of the Problem The Solution Of The Schrödinger mentioning
confidence: 99%
“…Therefore, the impurities may be in the QD and affect its properties. In this connection, there are a number of theoretical works [1][2][3][4][5][6][7][8][9], in which the energy spectra of donors and acceptors are determined as functions of the nanocrystal parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [38] used a similar orthonormal WF basis to study the effect of the magnetic field on the optical properties of spherical nanosystems of the core/shell type (MSQD with a single potential well). The use of exact solutions of the Schrödinger equation based on degenerate hypergeometric functions to study the binding energy of an electron and an impurity and the oscillator force of quantum transitions of quasiparticles in MSQD with two potential wells separated by potential barrier was demonstrated in [37,39]. It was shown that the calculated binding energy agrees well with the results obtained by other methods, and that the dipole moment of quantum transitions depends significantly on the ratio of MSQD potential well width as this affects the distribution of the electron density in the nanosystem.…”
Section: Introductionmentioning
confidence: 99%